Drivers of Forest Cover Change and Indicators of Climate Change in Katimok Forest Reserve - Jebiwott, Alice; Ogendi, G. M; Makindi, Stanley Maingi; Esilaba, Moses (My University, 2016)
The conversion of forests into other land uses as well as unsustainable utilization of forest resources leads to a reduction in the area, quality and quantity of the forest cover and ecosystem services. Changes in forest cover as a result of the resource strain imposed on the ecosystem can significantly affect the local climate in terms of temperature and rainfall. This study was carried out to assess the drivers of forest cover change in Katimok forest and the impacts that the changes have had on the local climate in terms of temperature and rainfall. Household questionnaires, field observations and focus group discussions were used to identify the drivers of forest cover and to assess the perceptions of the community on whether there had been changes in forest cover and local climate since 1985. Climatic data was obtained from Katimok meteorological station. Descriptive and inferential statistics were used to analyze the social data and climatic data. The results indicated that agriculture and logging were perceived as the major drivers of forest cover change. The results from the climate data shows a slight increase in temperature trend from 1985- 2012 with mean annual temperature range of +- 1.44561. Similarly, the rainfall data shows an increasing trend, though not significantly. The study indicates that the observed forest degradation is as a result of observed anthropogenic activities in and around the forest. Therefore, there is need to develop stringent policy measures and appropriate strategies that can alter this unfavorable situation and lead to conservation of this ecosystem.
Keywords: Climate Change; Forest Cover; Ecosystems; Degradation; Katimok Forest Reserve